1957
DOI: 10.3181/00379727-96-23390
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Plasma Erythropoietin in Hypoxic Rats with or without Kidney(s) and/or Spleen

Abstract: The presence of an erythropoietic factor in the plasma of animals subjected to hypoxic hypoxia has been reported recently by Stohlman( 1 ) and Prentice and Mirand( l a ) . Additional data from our laboratory bear out a time-concentration relationship of plasma erythropoietin (EPF) in hypoxic hypoxic rats. Knowing of this time-concentration of EPF, studies were carried out to determine whether this time-concentration relationship of plasma EPF can be altered in absence of the kidney (s) and/or the spleen. Jaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
14
0

Year Published

1960
1960
1990
1990

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(19 citation statements)
references
References 1 publication
5
14
0
Order By: Relevance
“…2, top), are in accordance with previous studies employing hypobaric (1,5,17,20,22,24,26,31) or also normobaric hypoxia (22). Although the reported time intervals after which peak serum levels were reached are variable, it appears to be a consistent finding that EPO titers do not remain at the elevated levels that are reached early upon hypoxia, but despite continued hypoxic exposure decline to values that are still above base line, but severalfold below peak concentrations.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…2, top), are in accordance with previous studies employing hypobaric (1,5,17,20,22,24,26,31) or also normobaric hypoxia (22). Although the reported time intervals after which peak serum levels were reached are variable, it appears to be a consistent finding that EPO titers do not remain at the elevated levels that are reached early upon hypoxia, but despite continued hypoxic exposure decline to values that are still above base line, but severalfold below peak concentrations.…”
Section: Discussionsupporting
confidence: 79%
“…Following acute hypoxic hypoxia, an increase in renal EPO mRNA has been demonstrated after 1 h (27), and circulating EPO increases within 1.5-2 h (27). Interestingly, it has been demonstrated that EPO levels reach maximal values after 6-24 h in rodents (1,5,15,17,20,22,26,31) and within 48 h in humans (1,24) and thereafter decline despite continued hypoxia. This early decrease in EPO levels occurs before red cell mass and therewith blood oxygen content has increased significantly (1,17,20,26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These results strongly suggest that the kidney produces an erythropoietic factor. In the rat, Jacobson and associates (16) and Goldwasser, Fried and Jacobson (30) have pointed out the lack of erythropoietic factor response to hypoxia after nephrectomy, but other workers did not obtain the same results (31). On the other hand, Erslev (27), working on the rabbit, concluded that the kidney did not play a role in erythropoietic function.…”
Section: Discussionmentioning
confidence: 99%
“…However, in inost species, smnall but detectable amounts of Ep are produced in the absence of both kidneys (3,4,35). The overwhelming evidence suggests that the liver is the major source of this extrarenal Ep (5,36).…”
Section: Discussionmentioning
confidence: 99%